An investigation of classroom intervention : plot as a pre-writing strategy on the narrative writing of ESL students / Gan Shiau Chin - Gan, Shiau Chin (2012)
Out of the four language skills, writing skills is said to be one of the harder skills for ESL students to master (Naginder Kaur, Nor Hayati Othman, & Abdullah, 2008; Sabariah Md. Rashid & Chan, 2008). Although writing is part of the major component being tested in the SPM English examination, yet many students with low level of English proficiency scores poorly for this component. One of the factors which lead to their poor performance in writing test is the lack of knowledge in pre-writing strategies. Pre-writing refers to the first stage of the writing processes, whereby one will spend some time to plan before attempting to produce a piece of writing. This study has incorporated the use of plot as a pre-writing strategy in instructing the students’ timed writing, specifically in the production of narrative essays. The research aims to investigate how pre-writing strategies affect the low and intermediate level of English proficiency students’ timed writing in terms of (i) essay scores, (ii) length, (iii) content and (iv) organisation. The mix-method approach was employed and the data was obtained via pre-test, post-test and interview sessions. The findings from the study revealed that the pre-writing strategy used has aided both groups of participants’ timed-writing in the four focused areas of this study, especially in terms of essay length. In lieu of the findings, it is crucial for main stakeholders such as the curriculum designers, test designers and teachers to attempt to use the process approach when it comes to the teaching of writing. When the students are aware of the process of writing, their writing skills will be enhanced, which translate to better writing scores during examinations.